Effects of an Electrode Gap on Efficiency of Electro-Coagulation Process in a Continuous-Flow Wastewater Treatment - ภักดี, วาทิต; รัตนพงศ์, กิตติพล (Engineering and Technology Horizons, 2020)
Wastewater treatment is essential in both industries and households. Ways or methodologies to develop effective treatment have been attracted widely. One of the processes used to treat waste water is an electro-coagulation (EC) process. In this process, contaminated particles are coagulated and can be separated from the waste water. This research studied effects of a distance between electrodes on the EC process efficiency. The important portion of the experimental system is a reactor that is composed of a number of electrodes made of aluminum plates. The spaces between electrodes of 4 6 8 and 10 mm were chosen. The reactive surfaces tested were 150×150 150×180 and 150×210 mm2. The samples being a flour solution and acrylic dye were tested in a continuous flow using a parallel and series electric circuit. The efficiency of the EC process was determined by the reduced turbidity, pH and power used. The turbidity was reduced more in the case of flour solution than acrylic dye after it was treated. It was found that EC process decreased the acidity of the treated water. When the spaces between the electrodes decreased, turbidity was reduced, but it required more power. The efficiency of the EC process in the flour solution is higher than in the acrylic dye.